Effusive-constrictive tuberculous pericarditis in the setting of penetrating abdominal trauma. (26th August 2015) - Meytes, Vadim; Docimo, Salvatore; Elkowitz, David; Kopatsis, Anthony
Abstract : Tuberculous pericarditis is rare in developed nations and is most commonly associated with effusive-constrictive pericarditis. We present the case of a 33-year-old man with a self-inflicted mid-abdominal stab wound. The patient underwent an exploratory laparotomy, revealing a grade IV pancreatic transection and injuries to the portal vein, right renal vein, inferior vena cava and the superior mesenteric vein. Repair of the vessels was performed and a pancreaticojejunostomy with a gastrojejunostomy was created for the pancreatic injury. The patient's hospital course was complicated by tuberculous effusive-constrictive pericarditis requiring emergent median sternotomy with opening of the pericardial sac and eventual expiration. The final cultures from the pericardial fluid demonstrated tuberculosis.